A water footprint assessment of dryland pasture based dairy enterprise in the Eastern Cape: a case study - Jenje, Paige (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2017)
Water scarcity continues to pose a threat to South Africa, with severe water scarcity predicted within the next fifty years. As a result, national interest has been sparked over the development of market based water resource allocation strategies to alleviate pressures on South Africa's freshwater resources, and ensure compliance with the National Water Act. Agriculture is the largest water user internationally and within South Africa, highlighting the importance of improving the water use efficiency within the industry. This study performed a full water footprint assessment (WFA) of a dryland pasture based dairy enterprise in the Eastern Cape. Following the guidelines of the WFA, this study calculated the blue, green and grey water footprints of dryland pasture based dairy production from crop- to-farm gate by assessing the water footprints of pasture production, bought in feed and concentrates, drinking water and servicing water processes over a period of five years. Following the accounting the of the water footprint, economic and environmental sustainability indicators were used along with the incorporation of the Water Risk Filter tool. This revealed that the case study farm was operating efficiently with the enterprise's highest water related risk being governmental regulation. Water footprint accounting results highlighted that green water was largest contributor to the overall water footprint of over 80%, and grey water contributed the least to the water footprint of dryland pasture based dairy production. Economic productivity results indicated that milk production is highly correlated with annual rainfall due to the breeding strategy undertaken by the farm. Results also indicated little correlation between the monthly water footprint and milk production, with the majority of the enterprise's milk production occurring in the last quarter regardless of the water footprint. The study demonstrated the relationship between the water footprint and economic land and water productivity, along with the value of milk to costs ratio which indicated that approximately R1.00 worth of costs generates between R1.80 and R2.06 value of milk. The sustainability indicators suggested that the farm's management of its effluent dam requires attention to meet the Department of Water and Sanitations effluent waste quality guidelines. The overall analysis of the water footprint suggested that the highest water related risk to dryland dairy production was regulatory risk. This risk suggests that the government cannot be relied upon for the management of freshwater resources within the study area, leaving the onus on the individual dairy farmers. As such, farmers should utilise the water footprint to formulate water stewardship programmes which have the potential to influence the regulation and protection of freshwater resources.
Keywords: Water supply, Agricultural -- South Africa; Water supply, Agricultural -- Government policy -- South Africa; Water consumption -- Measurement -- South Africa; Water demand management -- South Africa; Water-supply -- Accounting -- South Africa; Cattle -- Water requirements -- South Africa -- Cast studies